2018
DOI: 10.1002/ijc.31805
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of cadmium and lead in relation to breast cancer risk in three prospective cohorts

Abstract: Cadmium and lead have been classified as carcinogens by the International Agency for Research on Cancer. However, their associations with breast cancer risk are unknown despite their persistence in the environment and ubiquitous human exposure. We examined associations of circulating levels of cadmium and lead with breast cancer risk in three case-control studies nested within the Cancer Prevention Study-II (CPS-II) LifeLink Cohort, European Prospective Investigation into Cancer and Nutrition - Italy (EPIC-Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…This may explain the conflicting results when different indicators of exposure were used. For instance, an association was not observed between breast cancer risk and [Cd] b [ 163 ], while [Cd] u has been consistently associated with a significant increase in risk for cancer [ 164 ].…”
Section: Dosimetry and Nephrotoxicity Assessmentmentioning
confidence: 99%
“…This may explain the conflicting results when different indicators of exposure were used. For instance, an association was not observed between breast cancer risk and [Cd] b [ 163 ], while [Cd] u has been consistently associated with a significant increase in risk for cancer [ 164 ].…”
Section: Dosimetry and Nephrotoxicity Assessmentmentioning
confidence: 99%
“…The studies measuring individual cadmium levels from blood, urine, or toenails are not necessarily measuring the same timing of exposure. Most [153155, 159, 162, 163], but not all [158, 164], epidemiologic studies of postmenopausal women or all ages combined show risk estimates in the 0.73 to 1.01 range (Table 2). Two studies show greater risk associated with cadmium exposure for premenopausal women than for postmenopausal women [156, 165], whereas two other studies show the reverse [157, 166], with additional studies describing generally null associations for both groups [160, 161, 167, 168].…”
Section: Introductionmentioning
confidence: 99%
“…difference by ER status ( p = 0.11)0.72–1.41Highest (> 13.3) vs lowest (< 7.48 μg/day) quartile Eriksen (2014) [155]Dietary cadmiumDanish postmenopausal women23,815 total in cohort with 1390 breast cancer casesAll cases IRR 0.99ER+ IRR 1.00ER− IRR 0.880.87–1.130.85–1.150.62–1.22Per 10 μg/day increase in intake Adams (2014) [154]Dietary cadmiumPostmenopausal women aged 50–79 years155,069 total in cohort with 6658 casesHR 0.90n.s. difference by ER status0.81–1.00Highest (> 14.21) vs lowest (< 7.10 μg/day) quintile Adams (2016) [162]Urinary cadmiumPostmenopausal women ages ≥ 50 years in Women’s Health Initiative12,701 total in cohort with 508 cases and 1050 controlsAll HR 0.80ER+ HR 0.98ER−/PR- HR 0.880.56–1.140.87–1.070.70–1.11Highest (> 0.748) vs lowest (< 0.325 μg/g creatinine) quartileAll ages Sawada (2012) [159]Dietary cadmiumJapanese women aged 45–74 years48,351 females total in cohort with 402 breast cancer casesHR 0.870.61–1.23Highest (median 32.3) vs lowest (median 19.2 μg/day) tertile Nagata (2013) [164]Urinary cadmiumJapanese women ages ≥ 25 years153 cases from one hospital and 431 controls invited for breast cancer screeningOR 6.052.90–12.62Highest (> 2.620) vs lowest (< 1.674 μg/g creatinine) tertile Gaudet (2018) [163]Blood cadmiumCancer Prevention Study II women 47–85 years of age816 cases and 816 controlsAll RR 1.01ER+ RR 0.89ER− RR 0.960.76–1.340.62–1.270.44–2.09Continuous per μg/LItalian women aged 35–70 years292 cases and 294 controlsRR 0.800.61–1.03Continuous per μg/LSwedish women aged 30–61 years325 cases and 325 controlsRR 0.730.54–0.97Continuous per μg/LCombined 3 nested case-cohort studies1433 cases and 1435 controlsRR 0.840.69–1.01Continuous per μg/L Abbreviations: BCSC Breast Cancer Surveillance Consortium, CI confidence interval, EPA Environmental Protection Agency, ER estrogen receptor, HR hazard ratio, IRR incidence rate ratio, NHANES National Health and Nutrition Examination Survey, n.s . not statistically significant, OR odds ratio, RR relative risk…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological and toxicological studies have reported that lead exposure causes several diseases affecting the cardiovascular system such as hypertension [1] and chronic kidney disease [2,3], as well as the hepatic system [4]. In addition, lead is capable of inducing oxidative stress that damages the brain and affects the life course [5,6], and probably contributes to carcinogenesis [7,8].…”
Section: Introductionmentioning
confidence: 99%